Prevalence and correlates of malnutrition among elderly in an urban area in Coimbatore - Anil Chankaramangalam Mathew; Darsana Das; Saranya Sampath; M Vijayakumar; N Ramakrishnan; S L Ravishankar (Wolters Kluwer Medknow Publications, 2016)
Background: Different studies in India have shown that more than 50% of elderly population of India are suffering from malnutrition and more than 90% have less than recommended intake. Objectives: The aim of this study is to estimate the prevalence and correlates of malnutrition among elderly aged 60 years and above in an urban area in Coimbatore using Mini Nutritional Assessment (MNA). Methods: A cross-sectional study was conducted on 154 households and 190 elderly were interviewed. Nutritional status was assessed using the MNA questionnaire. Results: Mean (standard deviation) age of the total population (n = 190) was 71.09 (7.93) years and 30% was male. In this population, 37 (19.47%) was malnourished (MNA <17.0) and 47 (24.73%) were at risk for malnutrition (MNA 17.0-23.5). No significant association was observed between smoking, current alcohol consumption, higher medication use, higher comorbidity, and use of walk aid with malnutrition. Among the social factors studied, lower socioeconomic status compared to higher socioeconomic status (adjusted odds ratio [OR] =5.031, P < 0.001), single/widowed/divorced compared to married (adjusted OR = 3.323, P < 0.05), and no pension compared to those having pension (adjusted OR = 3.239, P < 0.05) were significantly associated with malnutrition. Conclusion: The prevalence of malnutrition observed in the aged people is unacceptably high. The increasing total number of lifestyle, somatic, functional, and social factors was associated with lower MNA scores. The findings of the present study clearly indicate that malnutrition is a multifactorial condition associated with sociodemographic, somatic, and functional status. Hence, we recommend that the treatment of malnutrition should be multifactorial, and the treatment team should be multidisciplinary. Further research is needed to develop appropriate guidelines for nutritional screening and interventional programs among geriatric population.